2009
DOI: 10.1158/0008-5472.can-08-4540
|View full text |Cite
|
Sign up to set email alerts
|

Differential Response of Glioma Cells to FOXO1-Directed Therapy

Abstract: Gliomas are the most common adult primary brain tumors, and the most malignant form, glioblastoma multiforme, is invariably fatal. The phosphatidylinositol 3-kinase (PI3K)-Akt signaling pathway is altered in most glioblastoma multiforme. PTEN, an important negative regulator of the PI3K-Akt pathway, is also commonly mutated in glioma, leading to constitutive activation of Akt. One ultimate consequence is phosphorylation and inactivation of FOXO forkhead transcription factors that regulate genes involved in apo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 49 publications
2
34
0
Order By: Relevance
“…The FoxO proteins (FoxO1, FoxO3a, FoxO4, and FoxO6) are key effectors of PI3K/Akt signaling and regulate many biological processes such as cell cycle progression and cell differentiation [16,26]. In addition, as a transcription factor, FoxO1 acts at a convergence point of several growth factor receptor tyrosine kinase pathways that may play central roles in glioma tumorigenesis [16,17]. In a previous study, Chen et al found that FF-induced lipid-lowering effects were associated with increased expression of FoxO1 in myotubes [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The FoxO proteins (FoxO1, FoxO3a, FoxO4, and FoxO6) are key effectors of PI3K/Akt signaling and regulate many biological processes such as cell cycle progression and cell differentiation [16,26]. In addition, as a transcription factor, FoxO1 acts at a convergence point of several growth factor receptor tyrosine kinase pathways that may play central roles in glioma tumorigenesis [16,17]. In a previous study, Chen et al found that FF-induced lipid-lowering effects were associated with increased expression of FoxO1 in myotubes [27].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, as a substrate of Akt, FoxO1 plays a causal role in tumor suppression and results in the transcriptional activation of p27 kip [15,16]. A recent study has shown that targeting FoxO1 could effectively induce glioma cell death and inhibit tumor growth by controlling the expression of cell cycle-related genes [17].…”
Section: Introductionmentioning
confidence: 99%
“…FoxO1 has emerged as an important effector arm of PI3K/Akt signaling that regulates multiple biological processes, such as cell differentiation and apoptosis [23]. In addition, as a transcription factor, FoxO1 acts at a convergence point of several growth factor receptor tyrosine kinase pathways and may thus play an important role in glioma tumorigenesis [30]. In the present study, we have shown that caffeine not only increases the expression of both FoxO1 and its proapoptotic target Bim but also promotes nuclear translocation of FoxO1 in U251 cells undergoing apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorylated Akt promotes cell survival, proliferation, and possibly other malignant properties such as motility and invasiveness by phosphorylating downstream targets such as anti-apoptotic protein Bax and forkhead box protein (FOXO) transcriptional factors [34,35]. The FOXO factors function as transcriptional activators and their activation regulates apoptotic responses, cell cycle arrest, and detoxification of reactive oxygen species as well as repair of damaged DNA [36][37][38]. Here, we did not study the role of BMI1 in the regulation of the Akt pathway.…”
Section: Discussionmentioning
confidence: 99%